(untitled) (Mustansiria Dental Journal, 2022)
Background: There are several different impression materials and techniques utilized in the fabrication of complete dentures. Aim of the study: To determine the anxiety levels and the clinical procedure time for maxillary completely edentulous patients by the use of two different impression techniques; the use of a low-fusing green stick compound along with zinc oxide eugenol impression paste and addition silicone (polyvinyl siloxane) along with light body material. Materials and Methods: Twelve maxillary edentulous subjects aged between 44 and 68 were randomly recruited for the study. After having the primary impression two special trays were fabricated for each patient; the first tray for the sectional border moulding group using impression compound along with ZOE final impression material (Group Z), and the second tray for the single-step border moulding technique using additional polyvinyl siloxane impression along with light body final impression materials (Group P). Comparisons between the two groups’ procedure time and patients’ visual analog scale (VAS) levels were made. Results: The results showed that group P had significantly reduced the VAS compared to group Z 17.5±12.88 and 57.5±16.03, respectively (P=0.000). The mean total procedure times for single-step border moulding and sectional border moulding impression techniques were 12.25±5.16 and 27.5±4.00, respectively (P=0.000). Also, a significant association between the treatment groups and VAS scores was observed by the multiple regression analysis model (P=0.000). Conclusion: As a result of the better patients’ perceptions and reduced clinical time, the study findings suggested using a single-step border moulding technique in the upper arch together with additional vinyl silicon material.